2008
DOI: 10.1007/bf03181932
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of turbulence structure in unsteady non-penetrative thermal convection using liquid crystal thermometry and stereo velocimetry

Abstract: Temperature and velocity fields in unsteady non-penetrative turbulent thermal convection of a horizontal fluid layer are measured in horizontal and vertical planes simultaneously using the combined liquid-crystal thermometry and stereo particle image velocimetry (PIV) with high spatial and temporal resolution. The result shows the formation of convection pattern across the fluid layer, which originates from the spoke structure over the heated surface. The upward fluid motion is generated from the intersection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Careful calibration is therefore essential to achieve measurements with a small uncertainty. Many reviews and papers have been published around the topic of LC thermography [7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Fujisawa N. and his group have produced many papers concerning this field [42][43][44][45]54].…”
Section: Liquid Crystal (Lc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Careful calibration is therefore essential to achieve measurements with a small uncertainty. Many reviews and papers have been published around the topic of LC thermography [7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Fujisawa N. and his group have produced many papers concerning this field [42][43][44][45]54].…”
Section: Liquid Crystal (Lc)mentioning
confidence: 99%
“…Many reviews and papers have been published around the topic of LC thermography [7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Fujisawa N. and his group have produced many papers concerning this field [42][43][44][45]54]. To study the transfer of heat and momentum in thermal fluid flow, the simultaneous measurement of temperature and velocity plays an important role in determining the physical properties of the transport phenomenon.…”
Section: Liquid Crystal (Lc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even more relevant for the present work is the combination of PIT and PIV used in [20][21][22] to measure the temperature and two components of the velocity fields in planes of a natural convection sample. The extension to the measurement of all three components of the velocity field simultaneous to the temperature field in planes was realized in an experiment with water by combining PIT with stereo PIV [23]. Fujisawa et al investigated the convection patterns by means of POD analysis and identified a large-scale motion.…”
Section: Introductionmentioning
confidence: 99%
“…Although 3-D velocity, concentration and temperature fields can be measured in a laboratory (Reungoat፧ et al, 2007;Fujisawa et al, 2008), the whole flow field measurement is very difficult in a real space such as a hospital room, which is always occupied by patients, or a domed baseball stadium, which has a large volume. Airflow distributions are usually measured with some sensors whose measured points are limited in the 3-D space.…”
Section: Introductionmentioning
confidence: 99%